1996
DOI: 10.1016/s0730-725x(96)00211-1
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic NMR investigation of the calcium silicate hydrates present in cement and concrete

Abstract: NMR spectroscopy is applied to study microstructure of calcium silicate hydrates present in cement and concrete. It is shown that 29Si NMR gives information on the siliceous skeleton of the hydrates. 1H NMR, using CRAMPS techniques, allows to discriminate between protons linked to silicon atoms or to calcium atoms. A first investigation of reference compounds indicates that 43Ca NMR will be powerful to determine calcium atom sites in the structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(122 citation statements)
references
References 9 publications
5
116
1
Order By: Relevance
“…All the diatomites show a major resonance at −110 ppm associated with the Q 4 groups in silica, as is typically found in biological systems, such as diatoms or sponges 28,29 . After 28 days of hydration, this main resonance shifts from −79 to −85 ppm, in the region of the Q 1 and Q 2 units in C–S–H, which appear at ≈−79 and −83 ppm, respectively 30,31 . Although the resonances in the hydrated materials are too broad and featureless to be deconvoluted with confidence, they show signs of underlying peaks in the form of shoulders in the positions of both types of C–S–H units.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…All the diatomites show a major resonance at −110 ppm associated with the Q 4 groups in silica, as is typically found in biological systems, such as diatoms or sponges 28,29 . After 28 days of hydration, this main resonance shifts from −79 to −85 ppm, in the region of the Q 1 and Q 2 units in C–S–H, which appear at ≈−79 and −83 ppm, respectively 30,31 . Although the resonances in the hydrated materials are too broad and featureless to be deconvoluted with confidence, they show signs of underlying peaks in the form of shoulders in the positions of both types of C–S–H units.…”
Section: Resultsmentioning
confidence: 76%
“…28,29 After 28 days of hydration, this main resonance shifts from À79 to À85 ppm, in the region of the Q 1 and Q 2 units in C-S-H, which appear at % À79 and À83 ppm, respectively. 30,31 Although the resonances in the hydrated materials are too broad and featureless to be deconvoluted with confidence, they show signs of underlying peaks in the form of shoulders in the positions of both types of C-S-H units. Because Q 1 groups are found on isolated pairs of Si tetrahedral, and Q 2 groups are located at the end of silicate chains, it is reasonable to conclude that the resulting silicate structure in the hydrated pastes is predominantly in the form of single dreierketten.…”
Section: Resultsmentioning
confidence: 99%
“…The 29 Si MAS NMR spectra of C-S-H (not shown) and C-S-HPN material contain mainly the Q 2 peak at about -84 ppm. However, a weak Q 1 peak or a shoulder is present in all spectra at about -79 ppm [35]. Acc o r d i n gt ot h e 29 Si MAS NMR spectra, it can be concluded that the C-S-H and C-S-HPN materials have the structure similar to that of tobermorite [35].…”
Section: Cp Nmr Andmentioning
confidence: 76%
“…The analysis is based on the Q n classification [35] where Q represents a SiO 4 4-unit and the degree of connectivity, n, is related to the oxygen bonds number between the SiO 4 4-units. The 29 Si MAS NMR spectra of C-S-HPN material are presented in Fig.…”
Section: Cp Nmr Andmentioning
confidence: 99%
“…Calcium-43 NMR has been used to study diverse compounds including simple salts, 24-26 small inorganic molecules and materials, 20,27-31 organic complexes, 32-34 protein-calcium complexes, 11,35-39 a calcium-nucleic acid complex, 40 hydroxyapatites, 41-44 minerals of importance to cement science, 17,45,46 superconductors, 47 amorphous slags and glasses, 9,48-50 polymorphs, 8,27 and inorganic polymers. 51 Smith and MacKenzie have presented an overview of 43 Ca SSNMR studies of inorganic materials up to 2001.…”
Section: Survey Of Data and Discussionmentioning
confidence: 99%